Eutectic behaviour of binary mixtures composed of two isomeric lactic acid derivatives. Issue 1 (2nd May 2016) - Bubnov, Alexej; Podoliak, Natalia; Hamplová, Věra; Tomášková, Petra; Havlíček, Jaroslav; Kašpar, Miroslav
ABSTRACT: Mixing of structurally similar self-assembling materials is a powerful tool to tune their mesomorphic, orientational or dielectric properties. We present design and study of binary mixtures composed of two newly designed chiral lactic acid derivatives with a similar structure but different geometry of the molecular core. One compound possesses a monotropic ferroelectric SmC* phase while another shows a direct isotropic – crystalline phase transition. It has been shown that the binary mixtures possess the eutectic behaviour and the ferroelectric phase temperature range has been extended. Moreover, for certain mixtures induced liquid crystalline phases, namely the cholesteric or TGBA phases, were detected.